PEDAGOGICAL STRATEGIES BY TEACHERS FOR IMPROVING PUPILS’ PERFORMANCE IN MATHEMATICS IN EDUCATION DISTRICT 5A, GRAND BASSA COUNTY, LIBERIA - Obumneke-Okeke, Ifeoma M.; Karnga, Morris Samuel (Journal of Early Childhood and Primary Education, 2025)
This study investigated pedagogical strategies employed by teachers to enhance pupils’ performance in mathematics in Education District 5A, Grand Bassa County, Liberia. Guided by three research questions, the study adopted a descriptive survey design. The population comprised 555 teachers across 89 primary schools, from which a stratified random sample of 75 mathematics teachers (45 males and 30 females) was selected to ensure proportional representation. Data were collected using a self-structured, 18-item instrument titled Pedagogical Strategies for Improving Pupils’ Performance in Mathematics Questionnaire (PSIPPMQ). The instrument was validated by experts, and reliability testing using Cronbach’s Alpha yielded a coefficient of 0.82, confirming strong internal consistency. Descriptive statistics, including mean and standard deviation, were employed to analyze the data. Findings revealed that teachers strongly endorsed hands-on instructional, problem-solving, and collaborative learning strategies as effective approaches to improving mathematics achievement. Problem-solving approaches fostered critical thinking, resilience, and contextual application of mathematics to everyday life. Collaborative learning strategies, including group projects, peer tutoring, and teamwork-based games, promoted motivation, communication, and shared responsibility, thereby strengthening both cognitive and social skills. It recommends deliberate integration of these strategies into classroom practice, supported by teacher training and curriculum development, to ensure sustainability. Collectively, these approaches provide practical, evidence-based solutions to address resource limitations and low performance in Liberia’s educational context, preparing pupils for future academic and professional success.